The Capitalisation of Area Payments into Farmland Rents: Micro Evidence from the New EU Member States - Pavel Ciaian; d'Artis Kancs (Economics and Econometrics Research Institute (EERI), 2009)
This study investigates the impact of the SAPS (Simplified Area Payment Scheme) on rental land values in seven New EU Member States (NMS). Using the FADN farm level panel data with 20,930 observations from 2004 and 2005 we are able to control for unobserved heterogeneity, simultaneity, and omitted variable bias, which often distort the incidence measures. According to our results, the SAPS has a positive and statistically significant impact on land rents in the NMS. However, the effect is smaller than theoretically predicted. Land rents capture only 0.19 of the marginal Euro of the SAPS. Taking into account the level of land renting in the NMS, around 10 percent of the total value of SAPS payments benefit non-farming land owners through higher farmland rental prices. Because the share of rented land is higher for corporate than for individual farms, family farms will likely benefit more from the SAPS than corporate farms.
Keywords: F12; L11; Q11; Q12; Q15; Q18; P32; R12; R23; 330; Agricultural policy; decoupled subsidies; capitalisation; land value